Histological and Biochemical Effect of Branded Energy Drink (Fearless) on the Liver and Kidney of Albino Rats - Tsennoe, Goyang J.; Tokwap, Gongmen T.; Gamde, Solomon M.; Ibanga, Imoh; Adisa, James O. (Transpublika Publisher, 2026)
Energy drink consumption is rising globally due to their perceived mental and physical performance benefits. These carbonated beverages contain high levels of caffeine, sugar, and various additives. This study examined the effects of the energy drink (Fearless) on liver and kidney histology and biochemical parameters in albino rats. Fifteen Rattus norvegicus (mean weight 126.3±23.9g) were divided into three groups (n=5): Group A (control) received standard feed and water; Groups B and C received 10 ml/kg and 20 ml/kg body weight/day of the energy drink for 6 weeks, respectively. The body weights of animals were measured. Following sacrifice under light anesthesia, blood samples were collected for biochemical analysis, and liver and kidney tissues were processed via paraffin wax for histological examination. Body weights of animals descriptively indicated steady increased. Biochemical analysis showed no statistically significant changes in the kidney function serum sodium, potassium, chloride, urea, and creatinine inclusive compared to controls. However, liver function parameters showed statistically significant elevations (P<0.05) in AST, ALT, and ALP in the test groups. Liver histology revealed central vein congestion and hepatocyte necrosis in both dose groups. The low-dose kidney sections exhibited glomerular tuft changes, polymorphonuclear inflammatory infiltration, architectural distortion, and vascular congestion, while the high-dose group showed widened Bowman's capsule space and renal tubule necrosis with inflammatory infiltration. These findings suggest that chronic energy drink consumption adversely affects liver and kidney structure and function.